Social justice in agroecology: co-creating equitable spaces for asylum seekers’ participation in Dutch Community Supported Agriculture (CSA) farms - Dondiego, Martina (2024)
Agroecology has gained global prominence as a framework for transforming food systems through ecological and social justice practices. Although it originated as an academic approach to applying ecological principles to agriculture, its meanings have evolved in different ways. In the Global North, agroecology is often associated with organic food production and consumer-driven environmentalism, sometimes failing to consider issues of equity, participation, and structural change. This tension is evident in Community Supported Agriculture (CSA) farms in the Netherlands. Although these farms are celebrated for promoting local, organic food and closer relationships between producers and consumers, they often remain exclusive spaces, serving predominantly white, educated, and middle- to upper-class consumers, therefore being of difficult access for marginalized groups. This thesis examines how grassroots agroecological initiatives can foster inclusion by co-creating spaces of participation for asylum seekers within Dutch CSA farms. It focuses on the work of Mycelia van Hoop, a working group within the Agroecology Network of the Netherlands, which has launched a pilot project to connect asylum seekers with CSAs. These efforts reflect a concrete commitment to placing social justice at the core of agroecological practice and challenging the gap between values and implementation. Using a mixed qualitative approach, this research aims to (1) map existing initiatives connecting asylum seekers with CSA farms; (2) identify the main barriers to participation, including logistical, cultural, and institutional factors; (3) explore the potential benefits of collaboration for both CSA farms and asylum seekers; (4) provide a practical framework and recommendations for fostering more inclusive agroecological spaces. By exploring the Dutch case, this thesis contributes to broader debates on the future of agroecology in Europe. It stresses the importance of claiming agroecology as a transformative project that not only promotes ecological resilience but also advances equity and solidarity. In doing so, it offers practical insights for policymakers, practitioners, and activists committed to making alternative food systems more just, inclusive, and participatory.